Innovation in Medicine and Healthcare 2017 Proceedings of the 5th KES International Conference on Innovation in Medicine and Healthcare (KES-InMed 2017) (Smart Innovation, Systems and Technologies,, 2018)
This volume focuses on smart medical and healthcare systems (modern intelligent systems for medicine and healthcare) and includes 31 papers presenting recent trends and innovations in medicine and healthcare, including biomedical engineering research and technologies; machine learning and labeling for biomedical visual data analysis and understanding; advanced ICT for medicine and healthcare; and healthcare support systems. Innovation in medicine and healthcare is an interdisciplinary research area, which combines advanced technologies and problem-solving skills with medical and biological science, and smart medical and healthcare systems can provide efficient and accurate solution to problems faced by healthcare and medical practitioners today by using advanced information communication techniques, computational intelligence, mathematics, robotics and other advanced technologies. Discussing the techniques developed in this area, which will have a significant effect on future medicine and healthcare, the book is a valuable resource for researchers, students, engineers, and professionals working in the fields of medical systems, medical technology, and intelligent systems.